Eficacia del score mamá para identificar riesgo obstétrico en embarazadas y puérperas indígenas. Hospital José María Velasco Ibarra, 2020 - Marlon Alcivar, Cuenca Ruiz (2021)
ABSTRACT Introduction: Maternal-fetal death is a public and social health problem, which is why the “Maternal Alarm” strategy has been developed to reduce maternal death that includes an early warning scoring system for maternal morbidity (MAMA Score), for the recognition and early response of the deterioration of clinical and physiological signs, and thus early identify obstetric pathology. Objectives: To investigate the efficacy of the MAMÁ score. To identify obstetric risk in indigenous pregnant and postpartum women at the José María Velasco Ibarra hospital in January - December 2020. Material and methods: a descriptive, retrospective, quantitative, qualitative, and crosssectional study was carried out, in which 365 obstetric patients self-identified as indigenous were collected, who were evaluated with the MAM Score. Results: The clinical histories of indigenous pregnant and postpartum patients were analyzed, and the score of the MOM Score obtained was related to the presence of obstetric complications that they developed, achieving a sensitivity of 77%, specificity of 66%, the positive predictive value of 32 % and negative predictive value of 93% to predict obstetric complications. Conclusions: The MAMA Score has a similar sensitivity to patients of non-indigenous ethnicity, but variations in specificity in indigenous patients, positive and negative predictive value, showing less specificity, so the MAM Score in indigenous patients would not be as effective as in patients of other ethnicities, detect healthy cases as negative casesKeywords: Score MOM. Hemorrhage before delivery. Hypertensive Disease of Pregnancy. Maternal Sepsis. Reviewed by: Mgs. Marcela González Robalino English Professor C.I. 0603017708